A influência do investimento em recursos intangíveis no desempenho das instituições financeiras estabelecidas no Brasil - Pires, Vanessa Martins (Universidade do Vale do Rio dos Sinos, 2017)
Strategic management fundamentally aims to understand the explanatory factors for heterogeneity in relation to organizational performance. The theoretical approaches in strategic management seek to meet this goal, considering external factors to organizations, such as strategic position and characteristics of the industry and internal factors such as resources, capabilities and competencies. Whereas that a great deal of organizational performance has been explained by internal factors, the Resource-based View (RBV) was used as a theoretical approach in this research. RBV assumes that having strategic resources provides superior performance. Organizational resources may be either tangible or intangible, and the latter typology has been recognized as a driver of organizational performance, thus being the object of this research. The literature that explores the relationship between intangible resources and organizational performance is limited, which raise some advances, such as: a) analyze intangible resources as a whole; b) consider more than one organization as a unit of analysis; c) contemplate longitudinal data; d) use a multidisciplinary approach and e) explore how intangible resources generate value. In view of this, the study intended to contribute to the overcoming of some limitations, identifying how the investments in intangible resources influence the performance of nineteen (19) publicly traded financial institutions established in Brazil. Therefore, the taxonomy for intangible assets developed by Kayo (2002) and Kayo et al. (2006) was used as a theoretical basis in the identification of investments in intangible resources, evidenced in management reports, financial statements and explanatory notes, quarterly, from 2008 to 2015. Based on market information and in accounting data regarding the performance of financial institutions, multiple linear regressions and a logistic regression were measured by using the Generalized Linear Model (GLM). The results indicated that, among the investments considered in the research, investments in human intangible resources are the greatest influence in the performance of the financial institutions studied. This research presents some contributions to the field of strategic management research, which are: a) the use of investments in intangible resources as proxies of the value of intangible resources and of accounting and market data regarding organizational performance; b) inquiries about the feasibility in operationalizing the theoretical presupposition of causal ambiguity in the analysis of the performance of intangible resources; c) the operationalization of intangible resources based on the theoretical model adopted, which includes the categorization of intangible resources and the importance of each of the categories (human, innovation, structure and relationship), considering the area of performance of organizations and the core competences required in each market.
Keywords: Visão baseada nos recursos; Recursos intangíveis; Ativos intangíveis; Desempenho organizacional; Instituições financeiras; Resource-based view; Intangible resources; Intangible assets; Organizational performance; Financial institutions; ACCNPQ::Ciências Sociais Aplicadas::Administração